Results of cementless humeral head resurfacing with cemented glenoid components - Raiss, Patric; Weiter, Manuela; Sowa, Boris; Zeifang, Felix; Loew, Markus (International orthopaedics, 2015)
The aim of this study was to analyse the short- and medium-term clinical and radiographic results of cementless humeral head resurfacing in combination with a cemented glenoid component.